A rare case of calcaneal bone osteomyelitis resulting from local paracoccidioidomycosis in an immunosuppressed patient: a case report - Santos, Eduardo Cezar Silva dos; Freitas, Cláudia Diniz; Romanholi, Pedro Bragato; Katayama, Martha Lúcia Silva; Pires, Eduardo Araújo; Silva, Daniel Araújo da (Journal of the Foot & Ankle, 2023)
Isolated bone involvement of paracoccidioidomycosis without any pulmonary focus is rare. This report documents the first case of calcaneal osteomyelitis, where bone infection was the only manifestation of the disease. A young 22-year-old male, mixed race, from a rural area in Brazil, was treated in the orthopedics emergency room. He reported a callus in the region of the Achilles tendon and developed intermittent claudication and, at times, inability to walk. In addition to having a low fever and sweating. He was hypertensive and on immunosuppressive medication due to a previous kidney transplant. An intracalcaneal collection was observed on magnetic resonance imaging, requiring surgical treatment for debridement and filling of the bone defect. After surgical intervention and administration of antifungal medication, the patient’s symptoms gradually improved. The epidemiological evaluation for differentialdiagnosis and the multidisciplinary clinical-orthopedic approach with effective diagnosis and treatment enabled the best clinical outcomes for the patient. Level of Evidence IV; Therapeutic studies; Case Report.